BioModels: Content, Features, Functionality, and Use. (26th February 2015) - Juty, N; Ali, R; Glont, M; Keating, S; Rodriguez, N; Swat, MJ; Wimalaratne, SM; Hermjakob, H; Le Novère, N; Laibe, C; Chelliah, V
Abstract : BioModels is a reference repository hosting mathematical models that describe the dynamic interactions of biological components at various scales. The resource provides access to over 1, 200 models described in literature and over 140, 000 models automatically generated from pathway resources. Most model components are cross‐linked with external resources to facilitate interoperability. A large proportion of models are manually curated to ensure reproducibility of simulation results. This tutorial presents BioModels' content, features, functionality, and usage. CPT Pharmacometrics Syst. Pharmacol. (2015) 4, 55–68; doi:10.1002/psp4.3 ; published online 25 February 2015